Foliar application of enriched banana pseudostem sap influences the nutrient uptake, yield, and quality of sweet corn grown in an acidic soil - Islam, Mahammad Shariful; Kasim, Susilawati; Amin, Adibah Mohd; Alam, Md. Khairul; Khatun, Mst. Fatima; Ahmed, Sharif; Gaber, Ahmed; Hossain, Akbar (2023)
Foliar fertilization is a reliable technique for correcting a nutrient deficiency in plants caused by inadequate nutrient supply to the roots in acid soil. Soluble nutrients in banana pseudostem sap might be effective to supplement chemical fertilizers. However, the limited nutrients in sole banana pseudostem sap as foliar fertilization may not meet-up the nutritional demand of the crop. Field trials were, therefore, conducted with the combination of soil-applied fertilizers with foliar spray of banana pseudostem sap to increase nutrient uptake, yield, and quality of sweet corn planted in acidic soil. Three treatments viz., 100% recommended dose of fertilizers (RD) as control (T1), 75% of RD applied in soil with foliar application of non-enriched banana pseudostem sap (T2), and 50% RD applied in soil with foliar spray of enriched banana pseudostem sap (T3) were replicated four times. The combination of soil-applied fertilizer with foliar spray of enriched banana pseudostem sap (T3) showed a significant increase in leaf area index (11.3%), photosynthesis (12%), fresh cob yield (39%), and biomass of corn (29%) over control. Besides, the 50% RD of soil fertilization with foliar spray of enriched pseudostem sap increased nutrient uptake in addition to an increase in sugar content, phenolic content, soluble protein, and amino acids of corn. Considering the economic analysis, the highest net income, BCR (3.74) and MBCR (1.25) values confirmed the economic viability of T3 treatment over the T1. The results suggest that foliar spray of enriched banana pseudostem sap can be used as a supplementary source of nutrients to enhance nutrient uptake by corn while increasing yield and minimizing chemical fertilizer use in acid soil.